The Effect of Fe Pillaring and Mg Intercalating into Bentonite Structure - Dian Maruto Widjonarko; Edi Pramono; Sentot Budi Rahardjo; Sayekti Wahyuningsih; Teguh Endah Saraswati (Jurnal Kimia Sains dan Aplikasi, 2026)
Bentonite clay particles, measuring less than 2 μm, comprise stacked layers of tetrahedral and octahedral units in a 2:1 configuration (T-O-T). These negatively charged layers were subsequently neutralized with cations. However, the exchange or modification of the cation affects its structure and properties. This study investigates the effect of Fe-ion pillaring on the bentonite layer and the intercalation of Mg ions into Fe-pillared bentonite via ion exchange. The materials were characterized using Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM–EDX) to observe surface morphology and elemental composition, Particle Size Analyzer (PSA) to observe average size and size distribution of particle, Fourier-Transform Infrared Spectroscopy (FTIR) to identify the active site and layer structure, and X-ray Diffraction (XRD) to determine their structural and compositional changes. The results confirm the pillaring treatment effect on a higher average particle size of 469.3 nm, with a polydispersity index (PDI) of 0.495, compared to natural bentonite (414.8 nm and 0.586 nm, respectively). Meanwhile, the intercalating treatment showed a lower average particle size of 433.4 nm and a PDI value of 0.613. FTIR identified the silanol and siloxane functional groups, as well as the aluminosilicate layer. Pillaring by Fe2O3 increased the basal spacing of bentonite from 13.6 Å to 17.35 Å, as indicated by the shift of characteristic bentonite peaks to lower 2θ angles. However, intercalation by MgO into Fe-pillared bentonite actually slightly decreased the basal spacing to 15.16 Å. Meanwhile, Mg intercalation occurred within the interlayer of the aluminosilicate layer, resulting in a peak shift toward higher 2θ angles and an increase in crystallinity to 58.924%, compared with Fe-pillared bentonite (45.376%). This phenomenon is likely related to the presence of the Mg metal intercalant, which has basic properties and can attract the aluminosilicate sheets.